Financial status of medical students in Institute of Medicine - Bhatta, V.R.; Joshi, A.B.; Jha, A.J.; Parajuli, P.; Koirala, S. (Journal of Institute of Medicine Nepal, 2007)
Background: Underrepresentation of students from low-income families at the Institute of Medicine in Maharajgunj (IOM) has been generally assumed. This study aims to assess the financial status of medical students at IOM to test the accuracy of that assumption. Methods: The study was conducted among 24th and 25th batch of students of IOM using pre-formed questionnaire. Results: The majority of students studying in IOM thought they have average to strong financial status and they felt little to no financial stress. Conclusion: Students from low income families are underrepresented in IOM.